SEMANTISCHE ANALYSE DES VERBS â€˜MACHENâ€˜ IN DER DEUTSCHEN SPRACHE - Dzanitsa Wide Febrianty; Ending Khoerudin; Putrasulung Baginda (Jurusan Pendidikan Bahasa Jerman FPBS UPI, 2023)
Predicate is an important particle to form a sentence in German language. Verb is a word which is designated to be the predicate in a sentence. The verb â€˜machenâ€™ is the German verb that has many meanings. It has various meanings which sometimes leads to confusion amongst the German learners. Moreover, it also affects the way a situation is described in a sentence. This study aims to: 1) find out the situation in a sentence which contains the verb â€˜machenâ€™ and 2) discover the meanings behind the verb â€˜machenâ€™ in various German articles. The data of this study is collected from a German online magazine, â€œDer Spiegelâ€. The method that the researcher used is descriptive qualitative. After every sentence that contains the verb â€˜machenâ€™ collected, classified, and analyzed, it can be said that the sentences with the verb â€˜machenâ€™ can be found in many more situation. This study concludes that there are 40 statement sentences and 10 questions which are found in 34 articles. There are 3 sentences that falls under the category of komplexe punktuelle ZustandsverÃ¤nderung, 16 which is classified as inkrementelle ZustandsverÃ¤nderung, and 21 which is counted as atelischer Ereignisbezug. The meanings of the verb â€˜machenâ€™ are cited from the online dictionary, â€œDUDENâ€. There are 20 kind of meanings of the verb â€˜machenâ€™. Based on the study, most of the verb â€˜machenâ€™ which is found in the articles can be explained as â€œEtwas tun (to do something), unternehmen (to do); sich etwas (Bestimmen) beschÃ¤ftigen (to occupy oneself with something)â€ with 21 sentences referring to it. On the other hand, the other meanings of the verb â€˜machenâ€™ are found in a more specific context.Â